2022
DOI: 10.1186/s12877-022-03699-9
|View full text |Cite
|
Sign up to set email alerts
|

The unmet needs of older adults living in nursing homes in Mainland China: a nation-wide observational study

Abstract: Background The unmet needs of older adults in nursing homes could result in their poor health status physically and psychologically. The aim of this study was to understand the characteristics of unmet needs of older adults residing in nursing homes in China, and to probe into the contributing factors. Methods In this cross-sectional design, the demographic and health status questionnaire, Modified Barthel Index, the Numerical Rating Scale for pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…China has the largest number of lung cancer patients, and the second largest number of related drug trials with the highest growth rate 8,18 . However, the setting of eligibility criteria in cancer drug trials in China has been found to be stricter than trials abroad in our study of age restriction 19 . Conducting sophisticated research and guiding the rational optimization of NSCLC drug trial eligibility criteria based on real‐world patients in China is of considerable clinical significance and value.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…China has the largest number of lung cancer patients, and the second largest number of related drug trials with the highest growth rate 8,18 . However, the setting of eligibility criteria in cancer drug trials in China has been found to be stricter than trials abroad in our study of age restriction 19 . Conducting sophisticated research and guiding the rational optimization of NSCLC drug trial eligibility criteria based on real‐world patients in China is of considerable clinical significance and value.…”
Section: Introductionmentioning
confidence: 95%
“…8,18 However, the setting of eligibility criteria in cancer drug trials in China has been found to be stricter than trials abroad in our study of age restriction. 19 Conducting sophisticated research and guiding the rational optimization of NSCLC drug trial eligibility criteria based on real-world patients in China is of considerable clinical significance and value. The remainder of the protocol details the primary aim, overall framework, and key design of the REC evaluation study concerning the risk-benefit profile of common regimens for NSCLC based on the integrated cross-dimensional RWD from China to be described in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Institutional care has become a primary way of retirement enjoyment for older adults. The older adults living in nursing homes are generally older, mainly aged 80 years and over, mostly widowed or divorced women with adult children (12). Most of them are sick and depend on others for help in their daily lives.…”
Section: Rationale For the Studymentioning
confidence: 99%
“…Currently, China is in the accelerated development of population aging, and it is of great practical significance to establish and improve the classified management system of nursing homes [6]. Formulating an evaluation index system and evaluation method specifically for public nursing homes is necessary.…”
Section: Improve the Nursing Home System And Organize Social Activiti...mentioning
confidence: 99%